La desigualdad social y las relaciones sociales de los moradores del barrio “San Pedro, Cañaveral”; Lago Agrio, en la actualidad - Salazar Campoverde, Johana Elizabeth (2024)
The importance of participating in the reduction of social inequality and how it affects social relations entails great challenges for the entire community, seeking to improve the quality of life by ensuring that all individuals have equal access to the opportunities and resources necessary for their social development; because, by reducing these inequality gaps in the communities, a more harmonious environment is promoted and possible confrontations or the development of previously unresolved disputes are prevented. In addition, relevant results were found such as the low economic status that prevails in approximately 80% of the families in the "San Pedro Cañaveral" neighborhood, this fact leads to the importance of acting in an emergent way in the creation of different strategies that contribute to the improvement of the well-being of the families. However, emerging variables such as social exclusion, mental health, and insecurity were also detected; these variables have been derived due to the lack of strengthening community ties which has prevented free socialization in the neighborhood. That is, not having a harmonious and non-hostile environment has even led to social distancing in the respective meetings that have been held in the sector, which are carried out in order to obtain different perspectives or opinions on the projects that need or will be implemented in the sector. Therefore, the research aimed to analyze the level of social inequality and social relations of the inhabitants of the neighborhood "San Pedro, Cañaveral" in the city of Lago Agrio, during the current period. For this purpose, a mixed methodological design was used, applying as techniques (semi-structured interviews, focus groups and sociodemographic survey) and as instruments (semi-structured guides, diffusion script and sociodemographic cards), applied to directors and residents of the neighborhood, with the purpose of validating the data through triangulation.